Discovery of potent antitubercular agents: Design, synthesis and biological evaluation of 4-(3-(4-substitutedpiperazin-1-yl)-quinoxalin-2-yl)-naphthalen-1-ol analogues. (August 2022) - Nandikolla, Adinarayana; Mahadu Khetmalis, Yogesh; Mahalakshmi Naidu, Kalaga; Karan Kumar, Banoth; Murugesan, Sankaranarayanan; Chandra Sekhar, Kondapalli Venkata Gowri
Abstract: A series of twenty-five novel 4-(3-(4-substituted piperazin-1-yl)-quinoxalin-2-yl)-naphthalen-1-ol analogues were synthesized, characterized and screened for in vitro antitubercular activity against Mycobacterium tuberculosis H37Rv strain. These compounds exhibited minimum inhibitory concentration in the range of 1.56–50 μg/mL. Among these derivatives, compounds 5a, 5b, 5f, 5m, 5p, and 5r displayed moderate activity (MIC 6.25 μg/mL). Compounds 5c, 5d, 5g, 5l, and 5o showed significant antitubercular activity (MIC 3.125 μg/mL), while compounds 5h, 5n, and 5q exhibited potent antitubercular activity (MIC 1.56 μg/mL). In addition, MTT assay was performed on the active analogues of the series against mouse macrophage cells to assess the cytotoxic effect of the newly synthesized compounds, and a selectivity index of the compounds was established. Selectivity index values of the most active compounds (5h, 5n, and 5q) are >47, indicating the compounds' suitability for further potential drug development. A molecular docking study was performed to understand the putative binding mode and binding strength of the selected significantly active and weakly active compounds with the target enzyme mycobacterial topoisomerase II using moxifloxacin as standard. In-silico ADME prediction and bioavailability studies of the titled compounds obey Lipinski's rule of five and Jorgensen's rule of three. To further ascertain the structure of the compounds, a suitable single crystal for the compounds 5a, 6, and 7d was developed and studied. Graphical abstract: Unlabelled Image Highlights: Synthesized and characterized 25 novel quinoxaline triazolyl derivatives. In vitro anti-TB activity against MTB H37Rv, using MABA method, was performed. 5h, 5n & 5q with MIC 1.56 and 5c, 5d, 5g, 5l & 5o with MIC 3.125 μg/mL were active. In-silico ADMET and docking studies for 5h and 7a were carried out and reported.